Pretreatment Hematologic Findings as Novel Predictive Markers for Facial Palsy Prognosis. (October 2016) - Wasano, Koichiro; Kawasaki, Taiji; Yamamoto, Sayuri; Tomisato, Shuta; Shinden, Seiichi; Ishikawa, Toru; Minami, Shujiro; Wakabayashi, Takeshi; Ogawa, Kaoru
Objective: To examine the relationship between prognosis of 2 different facial palsies and pretreatment hematologic laboratory values. Study Design: Multicenter case series with chart review. Setting: Three tertiary care hospitals. Subjects and Methods: We examined the clinical records of 468 facial palsy patients who were treated with an antiviral drug in combination with either oral or intravenous corticosteroids in participating hospitals between 2010 and 2014. Patients were divided into a Bell's palsy group or a Hunt's palsy group. We used the Yanagihara facial nerve grading system to grade the severity of facial palsy. "Recovery" from facial palsy was defined as achieving a Yanagihara score ≥36 points within 6 months of onset and having no accompanying facial contracture or synkinesis. We collected information about pretreatment hematologic findings, demographic data, and electrophysiologic test results of the Bell and Hunt group patients who recovered and those who did not. We then compared these data across the 2 palsy groups. Results: In the Bell's palsy group, recovered and unrecovered patients differed significantly in age, sex, electroneuronography score, stapedial muscle reflex, neutrophil rate, lymphocyte rate, neutrophil-to-lymphocyte ratio, and initial Yanagihara score. In the Hunt's palsy group, recovered and unrecovered patients differed in age, electroneuronography score, stapedial muscle reflex, monocyte rate, platelet count, mean corpuscular volume, and initial Yanagihara score. Conclusions: Pretreatment hematologic findings, which reflect the severity of inflammation and bone marrow dysfunction caused by a virus infection, are useful for predicting the prognosis of facial palsy.